Psychedelic Experiences During the Early COVID-19 Pandemic: Findings From an International Online Survey - Evens, Ricarda; Reiche, Simon; Marek, Roman M.; Moon, Daa Un; Groß, Rosa Elisa; Romanello, Amy; Jalilzadeh Masah, Dario; Scicchitano Böckheler, Matteo; Gutwinski, Stefan; Montag, Christiane; Mick, Inge; Majić, Tomislav (Frontiers in Psychiatry, 2021)
Introduction. The current corona virus disease (COVID 19) pandemic has caused a serious global health crisis that has affected large parts of the public and private life worldwide, including the use of psychoactive substances. In this study, we investigated the effect of the COVID 19 pandemic on the use of serotonergic psychedelics, i.e., the settings in which people use psychedelics, the motives of usage, and the subjective quality of psychedelic experiences. Methods. The study was part of an international, cross-sectional, internet-based survey (N = 5,049) available in 5 languages (English, German, Spanish, Italian and Korean) carried out during the early phase of the pandemic from April to August 2020. Participants were asked to retrospectively rate settings and motives of psychedelic substance use before the pandemic and in the last 4 weeks during the pandemic, as well as changes in psychedelic experiences. Results. Of n = 1,375 participants that reported the use psychedelics in 2019 or 2020, n = 642 (46.6% ) also took psychedelics during the pandemic. During the pandemic, participants used psychedelics significantly less often in settings that were outside their home. Top motives to use psychedelics were comparable before and during the pandemic, but participants consumed less out of curiosity, to celebrate, or because friends took it, and more out of boredom. An increase in positively connoted, often pro-social experiences was observed. Two thirds of participants who used psychedelics during the pandemic claimed that psychedelics had helped them to deal better with the corona pandemic at least slightly. Discussion. Changes in setting and motives were mostly in line with restrictions caused by control measures to contain the spread of the virus. The unexpected increase in positively connoted experiences possibly reflects a favorable interaction of environmental macro- and individual micro-contexts during the pandemic (e.g., by reducing the use in more uncontrolled recreational settings or by encouraging a strong self-selection of substance users due to the expectation of “bad trips”). Increased pro-social feelings under psychedelics might reflect a desire for social interactions in times of social distancing and pandemic-related stress and anxiety.